ORGANIZATION OF THERAPEUTIC PHYSICAL TRAINING IN THE NEUROSURGERY CENTER OF SAMARKAND STATE MEDICAL UNIVERSITY - Ravshanov Davron Mavlonovich (Research Focus International Scientific Journal, 2025)
This article presents modern approaches to organizing therapeutic physical training (TPT) at the Neurosurgery Center of Samarkand State Medical University. The rapid advancement of neurosurgical techniques now enables early medical rehabilitation of patients during the postoperative period. The paper highlights specific rehabilitation strategies for various neurosurgical conditions, including brain and spinal tumors, cerebral aneurysms, hematomas, subarachnoid hemorrhages, and severe traumatic brain injuries. It outlines the structure of rehabilitation programs, stages of mobilization, and the integration of orthopedic aids, massage, and physiotherapy. The study emphasizes that a comprehensive approach combining physical, psychological, occupational, and social rehabilitation significantly enhances recovery of motor, cognitive, and daily living functions in neurosurgical patients.